Ease and Limitations in Using Environmental DNA to Track the Spread of Invasive Host–Parasite Complexes: A Case Study of the Freshwater Fish Pseudorasbora parva and the Cryptic Fungal Parasite Sphaerothecum destruens - Théo Deremarque; Rodolphe Elie Gozlan; Ravo Ravaozafindrasoa; Giuliano Mucci; Lucie Delalex; Jean-Michel Foissy; Michaël Cagnant; Mathieu Clair; Justina Givens; Fabienne Justy; Alice Valentini; Delphine Nicolas; et al. (Fishes, 2024)
The spread of non-native species threatens biodiversity and exacerbates societal challenges like food security. To address this, effective conservation programs require detection methods that are easy to implement, accurate, and non-invasive. Over the past 15 years, environmental DNA (eDNA) techniques have gained popularity, surpassing traditional sampling methods. In this context, our study focused on tracking the invasive host–pathogen complex Pseudorasbora parva and Sphaerothecum destruens using eDNA metabarcoding. We collected water samples from freshwater canals over five months in the Camargue region, and once in Corsica Island, both in southern France. Total DNA was extracted from filtered water samples, and PCR-amplicons were sequenced using Illumina or Nanopore technologies. Our results revealed a high detection rate of P. parva in lentic ecosystems, aligning with habitat preferences of this small freshwater fish. Additionally, the detection rate in Camargue increased in May and June, likely due to the peak of the spawning season, which leads to more DNA being released into the environment (i.e., concentration and interaction of individuals). While eDNA successfully detected this invasive fish, we were unable to detect its cryptic fungal parasite, S. destruens, highlighting the challenges of identifying intracellular and cryptic fungal pathogens through eDNA methods.

Interaction between the severity of the infection by the nematode Anguillicola crassus and the tolerance to hypoxia in the European eel Anguilla anguilla - François Lefebvre; Pascal Contournet; Alain Crivelli (Acta Parasitologica, 2007)
An experiment was conducted to test the effect of the infection by the swimbladder nematode Anguillicola crassus on the survival of the European eel Anguilla anguilla when exposed to hypoxic conditions. Forty-four wild caught and naturally infected eels were placed in an aquarium filled with water from the fishing site (Vaccarès Lagoon, French Mediterranean coast). In this confined environment (271), under decreasing oxygen resources, the first eel death occurred after 45 h (O2 = 0.98 mg l−1) and the last one after 96 h (O2 = 0.48 mg l−1). After dissection and parasite examination, analyses revealed significant negative correlations between the time to death and various parameters of parasite pressure (e.g., number of lumen worms, parasite mass, health state of the infected organ). It was shown that the severity of damage to the swimbladder rather than the count of living parasites was the major contributing factor in explaining the variation in time to death. These semi-experimental data demonstrating an increased eel mortality rate under severe oxygen stress are discussed for their relevance under field conditions, especially during hot summer months.